Antenatal Diagnosis of Conjoined Twins - Parapagus Dicephalus A Case Report - Mummigatti, Kasturi; Shamshal, Aeda (Nepal Journal of Obstetrics and Gynaecology, 2011)
A case of 5 hour old, new born alive female baby laterally fused with two heads, two necks, one body with two legs and three fully formed upper arms and the 3rd arising between the two heads with Apgar score of one and five, diagnosed antenatally and born by Em CS Section at 32 weeks to a 30 year G7P5 with previous CS, died after five hours of birth, a severe lesion such as that found in this case of dicephalus parapagus conjoined twins which is incompatible with postnatal life account for less than 0.5% of all reported cases of conjoined twins who fail to survive is brought to discussion. Keywords: Parapagus, Dicephalus, Conjoined twins. DOI: http://dx.doi.org/10.3126/njog.v6i1.5256 NJOG 2011; 6(1): 61-65